Labour Markets in the Time of Coronavirus: Measuring Excess - Jonathan Wadsworth (Institute of Labor Economics (IZA), 2020)
No matter the cause, recessions are usually accompanied by some combination of job loss, hiring freezes, wage cuts or hours reductions. In a rapidly evolving economic crisis there is a need for timely information to assess labour market performance and develop strategies to address the problems that emerge. Household labour force surveys are not point-in-time data, but do offer the opportunity to analyse a broader range of outcomes not readily available in administrative data. They can also be utilised at higher frequencies than is normally associated with them. In what follows, the weekly information contained in the UK Labour Force Survey is tracked for several labour market outcomes from the first week of 2020 and onward as the Covid-19 crisis developed in spring 2020. The indicators are presented in "excess" form to gauge how far the 2020 incidence of a particular outcome differs from its weekly norm. It seems that the most common metrics of labour market performance, like unemployment or wage rates, show little departure from recent norms over the first few months of the crisis. The initial margins of adjustment were instead some cumulative 50 million more weekly workplace absences than usual during lockdown, notable hours reductions of up to 25% among the majority who carried on working, together equivalent to around 3 weeks of lost working for the whole workforce, allied to a notable stalling of hiring that had already begun several weeks before lockdown.
Keywords: J0; J3; J6; 330; COVID-19; unemployment; hours; wages; hiring